The Relationship Of School Health Enterprises (Uks) To The Level Of Knowledge About Reproductive Health Of Muhammadiyah Junior High School 5 Padang In 2023 - Hamidah, Waldatul; Zahara, Wahyuni (Alifah Health Science Symposium Proceeding, 2023)
Adolescent reproductive health is a healthy condition that concerns the system, function and process of adolescent reproduction. The results of the 2012 KRR IDHS show that adolescent knowledge about reproductive health is inadequate. It can be seen that only 5.4% of women and 7.2% of men know about adolescent reproductive health information and counseling services. To determine the relationship between the role of UKS and the level of knowledge about reproductive health of students at SMPN 6 Bukittinggi. The research design uses analytical research with a cross sectional study method. The research was conducted on 20 22 February 2018 at Muhammadiyah 5 Padang Middle School. The population in this study was all 67 students of class IX 5 and class IX 6 of. Sampling was carried out by total sampling, data processing was carried out using univariate and bivariate analysis (Chi-Square Test). The research results showed that of the 67 respondents who said the UKS role was inactive and whose knowledge was low, 42 respondents (62.7%) were respondents. The results of the bivariate analysis show that there is a significant relationship between the role of the UKS and students' knowledge (p = 0.000 and with an OR value = 8.924. The results of this research conclude that there is a relationship between the role of the UKS and the level of students' knowledge about reproductive health education. It is hoped that respondents can increase their knowledge about education reproductive health by following counseling from the School Health Business.